2008
DOI: 10.1108/14684520810914016
|View full text |Cite
|
Sign up to set email alerts
|

Structured versus unstructured tagging: a case study

Abstract: PurposeThis paper seeks to describe and discuss a tagging experiment involving images related to Israeli and Jewish cultural heritage. The aim of this experiment was to compare freely assigned tags with values (free text) assigned to predefined metadata elements.Design/methodology/approachTwo groups of participants were asked to provide tags for 12 images. The first group of participants was asked to assign descriptive tags to the images without guidance (unstructured tagging), while the second group was asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 10 publications
0
34
0
1
Order By: Relevance
“…This undermines the role of social tags as a meaningful bridge (Smith, 2006). Bar-Ilan, Shoham, Idan, Miller, and Shachak (2008) proposed that structured tags can help overcome these limitations by facilitating a deeper understanding about contents compared to the conventional tag cloud, which is an unstructured set of tags. Hearst (2006) also wrote that structured tags allow users to understand better the relationships between tags and make a quicker decision about how to use this information.…”
Section: Social Tagging Systems For Artworkmentioning
confidence: 98%
“…This undermines the role of social tags as a meaningful bridge (Smith, 2006). Bar-Ilan, Shoham, Idan, Miller, and Shachak (2008) proposed that structured tags can help overcome these limitations by facilitating a deeper understanding about contents compared to the conventional tag cloud, which is an unstructured set of tags. Hearst (2006) also wrote that structured tags allow users to understand better the relationships between tags and make a quicker decision about how to use this information.…”
Section: Social Tagging Systems For Artworkmentioning
confidence: 98%
“…Many studies have shown that, although professionals cannot be replaced, social tags enhance the description of images for users and provide data useful for retrieval. Bar-Ilan, Shoham, Idan, Miller, and Shachak (2008) found that for image retrieval, structured tagging done by professionals remains the best method for successful retrieval. However, credence should be paid to social tagging (Unstructured tagging) as it allows for a wider range of tags that may prove more useful in completing successful queries.…”
Section: Related Workmentioning
confidence: 98%
“…Wolfram, Olson, and Bloom (2009) emphasized the importance of this sort of work when they stated that "it is worthwhile to explore potential parallel characteristics between indexing and tagging as these characteristics could influence the form of tagging offered in a given situation and how tagging influences retrieval" (p. 1996) and called for a better understanding of the nature of tags. Others (Bar-Ilan, Shoham, Idan, Miller, & Shachak, 2008) have also called for studies on the strengths and shortcomings of tags and conventional indexing methods. To clearly define the research problem, a review of the phenomenon of social tagging and literature on indexing in general and image indexing in particular is necessary.…”
Section: Introductionmentioning
confidence: 99%